2022
DOI: 10.1029/2022jd037123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Arctic and Antarctic Stratospheric Climates in Chemistry Versus No‐Chemistry Climate Models

Abstract: Using nine chemistry‐climate and eight associated no‐chemistry models, we investigate the persistence and timing of cold episodes occurring in the Arctic and Antarctic stratosphere during the period 1980–2014. We find systematic differences in behavior between members of these model pairs. In a first group of chemistry models whose dynamical configurations mirror their no‐chemistry counterparts, we find an increased persistence of such cold polar vortices, such that these cold episodes often start earlier and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…Some of those biases in the Northern Hemisphere stratosphere are also found in the Southern Hemisphere counterpart (Rao and Gar nkel 2021b). For example, comparing CMIP5 models, the intermodel spread in the SFW date for the low-top model ensemble is wider and more pronounced than for the high-top model ensemble (Wilcox and Charlton-Perez 2013), which is consistent with the stratospheric ozone content especially for the chemistryclimate coupled models with interactive ozone (Haigh and Roscoe 2009;Morgenstern et al 2022). In addition, differences in the seasonal response of stratosphere to Antarctic sea ice loss is found among CMIP5 models (England et al 2018;Ayres and Screen 2019).…”
Section: Introductionmentioning
confidence: 74%
“…Some of those biases in the Northern Hemisphere stratosphere are also found in the Southern Hemisphere counterpart (Rao and Gar nkel 2021b). For example, comparing CMIP5 models, the intermodel spread in the SFW date for the low-top model ensemble is wider and more pronounced than for the high-top model ensemble (Wilcox and Charlton-Perez 2013), which is consistent with the stratospheric ozone content especially for the chemistryclimate coupled models with interactive ozone (Haigh and Roscoe 2009;Morgenstern et al 2022). In addition, differences in the seasonal response of stratosphere to Antarctic sea ice loss is found among CMIP5 models (England et al 2018;Ayres and Screen 2019).…”
Section: Introductionmentioning
confidence: 74%
“…Lastly, we comment on the possible role for interactive chemistry in driving inter‐model differences in the DJF precipitation change signal. Recent CMIP6‐based studies (Morgenstern et al., 2022; Revell et al., 2022) have shown that models with interactive chemistry (vs. without) show a significant difference in their projections for near‐surface temperature and windspeed for DJF in the Southern Hemisphere mid to high‐latitudes, presumably (in part) due to the importance of how stratospheric ozone is represented in the models. However, this appears less relevant for the precipitation change signal directly over New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…One downside of the ACCESS-CM2-Chem, relative to the version without interactive chemistry, is the exacerbation of the delay in vortex break-up. Morgenstern et al (2022) finds a related problem, namely the overly long persistence of cold polar stratospheric temperatures, in many CCMI-2022 models relative to their non-interactive chemistry counterpart. Noting the exceptions to this finding that occur in model pairings where there are also some additional non-chemistry differences (e.g.…”
Section: Summary and Discussionmentioning
confidence: 99%